Waste Retribution Optimization Strategy to Increase PAD in Karang Berombak Village, Medan City (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2025)
This study aims to examine the strategy of optimizing waste retribution and its impact on increasing Local Original Income (PAD) in Karang Berombak Village, Medan City, using a literature study method. The data used are sourced from various relevant online references, such as scientific articles, research results, and policy publications. Data collection techniques are carried out through literature reviews that include statistical data, policy analysis, and case studies that are in accordance with the focus of the study. The results of the study indicate that optimizing waste retribution in order to increase PAD requires a comprehensive approach. The strategy includes structured planning, consistent supervision, increasing public awareness and participation, and providing adequate facilities and infrastructure. The implementation of this strategy in an integrated manner is expected to encourage the effectiveness of waste retribution management and contribute significantly to increasing PAD in Karang Berombak Village.